Programme Planning in School: Perspectives on Out-Door Programme - Bridget, Ikegwuru (Richtmann Publishing, 2011)
He objective of this paper is to emphasize the need and importance of outdoor learning in our secondary schools whichwill act as a panacea to improving academic excellence and discipline in schools. It is believed that refocusing the out doorlearning will go a long way to strengthen the social, skills and mental development of the students. The methodology hereinvolves the review of the past and present perception of school head on outdoor programmes. It also finds out that theawareness is not there among the stakeholders in education. It was also discovered through personal interaction with staff andstudents that most schools do not take part in outdoor programme. Most of the schools interacted with show no knowledge ofwhat outdoor programmes are. The uniqueness of this paper is providing clues on how school head can introduce and carry outthe outdoor programmes. They should see it not as extra curricula activity but as an inevitable part of completing the schoolcurriculum. This paper is calling for a refocus on the outdoor learning and how this can be achieved internally without waiting forfund from the government but as a means of attracting the government.